English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

5
å (2^-k - 2^(-k - 1)) =
k=1

if this helps my book gives these possible solutions.

a. 31/64
b. -21/64
c. 63/64
d. 21/32
e. none of these

2006-12-10 04:35:29 · 4 answers · asked by Doug 2 in Science & Mathematics Mathematics

4 answers

Explain to me what you wrote above, please

Ana

2006-12-10 04:38:35 · answer #1 · answered by Ilusion 4 · 0 0

it is summation of 2^-k-2^(-k-1) from k=1 to k=5
k=1 2^-1-2^-2=1/2-1/2^2=1/2^2
k=2=1/2^3
k=3=1/2^4
k=4=1/2^5
k=5=1/2^6
adding
=1/2^2+1/2^3+1/2^4+1/2^5+1/2^6
=16+8+4+2+1/64
=31/64

2006-12-10 04:43:51 · answer #2 · answered by raj 7 · 2 0

I guess you made a couple of mistakes in typing the equation.

2006-12-10 04:42:54 · answer #3 · answered by ravish2006 6 · 0 0

this part .... (2^-k - 2^(-k - 1)) =
looks like
(2 exponent -k - 2 exponent -k - 1)

now how to solve
>??? I don't know

2006-12-10 04:47:03 · answer #4 · answered by Olivia 4 · 0 2

fedest.com, questions and answers